Daphniphyllum Alkaloids: Recent Findings on Chemistry and Pharmacology - Wu, Haifeng; Zhang, Xiaopo; Ding, Lisheng; Chen, Shilin; Yang, Junshan; Xu, Xudong (Planta Medica, 2013)
The unique polycyclic fused ring systems of Daphniphyllum alkaloids, along with their extensive bioactivities, make this family of alkaloids especially attractive targets for total synthesis and biogenetic studies. Successive discoveries of new alkaloids with unprecedented skeletons have made a great contribution to structural diversities of alkaloids elaborated by plants of the genus Daphniphyllum. By the end of 2008, more than 200 alkaloids belonging to 14 different skeletal types have been isolated from different parts of plants of thirteen Daphniphyllum species. These alkaloids show cytotoxic, antioxidant, vasorelaxant, and antiplatelet activating factor effects. The plausible biosynthetic pathways for Daphniphyllum alkaloids have been proposed and biomimetic total syntheses of some alkaloids completed. To provide an update of the previous reviews published in 2009, new structures, synthesis, and bioactivity of Daphniphyllum alkaloids reported in recent years are presented in this article. In the meantime, an additional 54 novel alkaloids have been isolated and identified. Among them, some possess unprecedented frameworks. Several inspired organic syntheses were completed.
Keywords: Daphniphyllum; Daphniphyllaceae; alkaloids; synthesis; biological activity